Hasan Hanafi And The Idea Of Deconstruction Of ScienceUshul Fiqh Towards The Reactualization Of Islamic Law - Badruzaman; Hakiki, Kiki Muhamad (AL-ADYAN, 2023)
This research examines Hasan Hanafi's thoughts on the deconstruction of ushul fiqh science as an effort to reactualize Islamic law. The results showed four main findings. First, Hasan Hanafi pays great attention to the revitalization of ushul fiqh through a historical approach, by emphasizing the importance of the historical and human dimensions in understanding the concept and methodology. This dimension is actually inherent in the classical methodology of ushul fiqh, but has been obscured as the discipline has developed. For Hanafi, the historical dimension is present in all elements of ushul fiqh, including adillah syar'iyyah, thuruq al-istinbath, and al-ahkam al-syar'iyyah, which are represented through the keywords "history" and "human". Second, the revitalization offered by Hanafi is a methodological update that adapts ushul fiqh to social reality, humanity, and the development of science, without breaking away from the traditions and treasures of classical scholars. Third, Hanafi's thinking is considered relevant for the reactualization of Islamic law because it is able to respond to the dullness and freezing of ushul fiqh by reviving its vital spirit and elan through a historical approach. Fourth, the historical idea is rooted in Hasan Hanafi's great project of al-Turats wa al-Tajdid, which views the loss of the human and historical dimensions as the cause of the stagnation of the progressivity of Muslim thought and praxis. Thus, this framework offers a conceptual basis for contextual readings of Islamic law that are adaptive, critical, rooted in tradition, and responsive to the challenges of global contemporary times.